The CCP's Central Committee Departments (1921-1991): A study of evolution - Kampen, Thomas (China report, 1993)
Since the founding of the PRC, the Chinese government has publicised the names of its ministers and ministries, but the Chinese Communist Party (CCP) has only reluctantly identified its Central Committee (CC) departments and their directors. However, in socialist countries these departments are often more important than ministries, and department directors enjoy more influence than Ministers. In this study the author describes and analyses the CC departmens of the CCP paying special attention to the Organization, Propaganda and International Liaison Departments. (DÜI-Sen)